HACS: Helical Auxetic Yarn Capacitive Strain Sensors with Sensitivity Beyond the Theoretical Limit. Issue 10 (6th January 2023) - Cuthbert, Tyler J.; Hannigan, Brett C.; Roberjot, Pierre; Shokurov, Alexander V.; Menon, Carlo
Abstract: The development of flexible strain sensors over the past decade has focused on accessing high strain percentages and high sensitivity (i.e., gauge factors). Strain sensors that employ capacitance as the electrical signal to correlate to strain are typically restricted in sensitivity because of the Poisson effect. By employing auxetic structures, the limits of sensitivity for capacitive sensors have been exceeded, which has improved the competitiveness of this modality of sensing. In this work, the first employment of helical auxetic yarns as capacitive sensors is presented. It is found that the response of the helical auxetic yarn capacitive sensors (termed as HACS) is dependent on the two main fabrication variables—the ratio of diameters and the helical wrapping length. Depending on these variables, sensors that respond to strain with increasing or decreasing capacitance values can be obtained. A greater auxetic character results in larger sensitivities accessible at smaller strains—a characteristic that is not commonly found when accessing high gauge factors. In addition, the highest sensitivity for auxetic capacitive sensors reported thus far is obtained. A mechanism of sensor response that explains both the variable capacitance response and the high gauge factors obtained experimentally is proposed. Abstract : Capacitive strain sensors are theoretically limited in their sensitivity. In this work, stretchable and flexible strain sensors are fabricated using a helical auxetic yarn structure providing access to auxetic character in the fiber form. The helical auxetic capacitive sensors (HACS) are able to access sensitivity beyond the theoretical limit, determined to be because of an engulfment phenomenon that occurs as a result of the materials employed and the auxetic character.